Numerical simulation of seismic wave propagation in media with viscoelastic intrusions - Vishnevsky, D.M.; Lisitsa, V.N.; Reshetova, G.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2013)
Seismic attenuation is a widespread property of the Earth’s interior due to low consolidation and fluid saturation of the rocks. However, viscoelastic formations typically take as few as 10 to 20% of the model. Thus, the use of computationally intensive algorithms, oriented on viscoelasticity, in the entire computational domains makes the simulations inefficient. In this paper an original algorithm based on the coupling of the elastic and viscoelastic statements is presented. The computationally intensive approach is used only in subdomains embedding the viscoelastic formations, whereas the ideal elastic equations are solved elsewhere. As a result, the speed-up of the hybrid algorithm is 1.7 compared to a purely viscoelastic implementation.